Deciphering the functional nano‐anatomy of the tripartite synapse using stimulated emission depletion microscopy - Arizono, Misa; Nägerl, U. Valentin (Glia, 2022)
A major challenge for studying neuron‐astrocyte communication lies in visualizing the tripartite synapse, which is the physical site where astrocytic processes contact and interact with neuronal synapses. While conventional light microscopy cannot resolve the anatomical details of the tripartite synapse, electron microscopy only provides ultrastructural snapshots that tell us little about its living state and dynamics. Stimulated emission depletion (STED) microscopy is a super‐resolution fluorescence imaging technique that can provide live images of tripartite synapses with nanoscale spatial resolution. It is compatible with physiology experiments and imaging in the intact brain in vivo, opening up new opportunities to link the nanoscale structure of the tripartite system with functional readouts of neurons and astrocytes or even behavior. In this review, we first summarize the findings and insights from previous studies addressing the structure–function relationship of the tripartite synapse using conventional imaging techniques. We then explain the basic principle of STED microscopy and the main challenges facing its application to live‐tissue imaging of fine astrocytic processes. We summarize insights from our recent STED studies, which revealed new aspects of the structure and physiology of the tripartite synapse and the surrounding extracellular space. Finally, we discuss how the STED approach and other advanced optical techniques can illuminate the role of astrocytes for brain physiology and animal behavior. Main Points While regular light microscopy cannot resolve tripartite synapses, EM only provides ultrastructural snapshots. STED microscopy can provide live images of them, including the extracellular space, enabling structure‐function studies at the nanoscale.